Business process reengineering in health-care sector: application for the central sterilization unit. Issue 2 (12th July 2021) - Dursun, Mehtap; Fındık, S. Sirin; Goker, Nazli
Abstract : Purpose: In a rapidly changing environment, many health-care systems are forced to survive with rising costs and the need for proper resources utilization. To address the requirements for effective strategic planning, business process reengineering (BPR) is inevitable for health-care systems. This study aims to focus on the reengineering of central sterilization unit's business processes to obtain performance improvement and efficiency. With the obtained new process design, it is expected to get standardization in all level of the central sterilization unit. Design/methodology/approach: This paper presents a BPR method for modeling the system in health-care sector to improve the productivity of the sterilization process of surgical equipment. The case study is conducted in a large hospital in Istanbul, Turkey. First, "as-is" process is modeled and the problems are determined. Then, solution methods are developed and the target system (to-be process) is redesigned and the workflows of each phase are remodeled by using ARIS tool. Enterprise resource planning (ERP)-driven BPR is used to reengineer the current processes and the future processes are operated through the modeled ERP system. Finally, by using a statistical analysis, performance of the new process is compared with the existing process using the first data obtained from the case hospital. Findings: In many sterilization services, the control procedures are rarely used. Thus, an ERP solution is developed to automate sterilization tasks and track down the information flow. With the ERP solution, it is possible to track in which dates, where and by whom the items are processed. On the other hand, in the sterilization process, the sets are used efficiently according to the last sterile dates of the items. Also, with the ERP system, it is possible to reduce unnecessary paper usage and this gives the hospitals the opportunity to be more ecological and sustainable. As a result, a centralized sterilization process with an IT support provides efficiency, economy and patient safety. Originality/value: This study seeks for the potential benefits of an ERP implementation in health-care sector. As a result of this project, improvements in productivity, cost and quality are expected in sterilization processes because the new process design will bring automation, human-related error reduction and equipment tracking system. For this purpose, a business process management software is developed and implemented to the central sterilization unit so that the information flows more safely and the managers can track the results quickly by charts and reports.